Brief Exercise Increases Peripheral Blood NK Cell Counts without Immediate Functional Changes, but Impairs their Responses to ex vivo Stimulation - Millard, Anne-Laure; Valli, Piero V.; Stussi, Georg; Mueller, Nicolas J.; Seebach, Jörg D. (Frontiers in Immunology, 2013)
Physical as well as psychological stress increases the number of circulating peripheral blood NK cells. Whereas some studies found a positive correlation between exercise and NK cell counts and cytotoxic activity, others showed that, for example, heavy training leads to a decrease in per cell NK cytotoxicity. Thus, the impact of exercise on NK cell function and eventually on altered immunocompetence remains to be elucidated. Here, we investigated whether a single bout of brief exercise, consisting in running up and down 150 stair-steps, affects the number and function of circulating NK cells. NK cells, obtained from 29 healthy donors, before and immediately after brief exercise, were assessed for numbers, phenotype, IFNγ production, degranulation, cytotoxicity, and in vitro response to stimulation with IL-2, IL-2/IL-12, or TLR2 agonists. Running resulted in a sixfold increase in the number of CD3−/CD56+ NK cells, but decreased the frequency of CD56bright NK cells about twofold. Brief exercise did not significantly interfere with baseline IFNγ secretion or NK cell cytotoxicity. In vitro stimulation with IL-2 and TLR2 agonists (lipoteichoic acid, and synthetic triacylated lipopeptide Pam3CSK4) enhanced IFNγ-secretion, degranulation, and cytotoxicity mediated by NK cells isolated pre-exercise, but had less effect on NK cells isolated following exercise. There were no differences in response to combined IL-2/IL-12 stimulation. In conclusion, having no obvious impact on baseline NK functions, brief exercise might be used as a simple method to significantly increase the number of CD56dim NK cell available for in vitro experiments. Nevertheless, the observed impaired responses to stimulation suggest an alteration of NK cell-mediated immunity by brief exercise which is at least in part explained by a concomitant decrease of the circulating CD56bright NK cell fraction.